Ethnische Unterschiede bei den Autoantikörper bei systemischer Sklerose (Aktuelle Rheumatologie, 2017)
Nandiwada SL et al. Ethnic Differences in Autoantibody Diversity and Hierarchy: More Clues from a US Cohort of Patients with Systemic Sclerosis.